Literacy in CPR a training handbook for school teacher / Muhamad Nur Fariduddin ...[et al.] - Nur Fariduddin, Muhamad; Mohamed, Mawarni; Jaafar, Mohd Johar (UiTM Press, 2024)
This training handbook is dedicated to all the school teachers across Malaysia who have contributed their time and effort to support the needs of teaching life-saving techniques and skills to all school students. The treatment recommendations and related training guidelines included in this handbook were adopted and adapted from the international guidelines and have been reviewed by the respective advisory council, a panel of internationally recognised experts in fields that include emergency medicine, occupational health, sports medicine, school and public health and emergency medical services (EMS). However, additional round of reviews was conducted locally through the selected experts from various fields to ensure its reliability.